Perbandingan Model Kooperatif Tipe Numbered Head Together (NHT) dan Group Investigation (GI) Terhadap Hasil Belajar Siswa Kelas X SMAN 8 Gowa - Arwina Husniawati Husain; Nur Khalisah Latuconsina; Lisnasari Andi Mattoliang; Ahmad Farham Majid; Nur Miftahul Jannah (Alauddin Journal of Mathematics Education, 2023)
This study aims to determine the comparison of cooperative learning models of the Numbered Head Together (NHT) and Group Investigation (GI) types of learning outcomes for class X students of SMAN 8 Gowa. This type of research is a quasi-experimental design with a Non-equivalent Control Group Design. The population in this study were students of class X MIPA which were divided into 7 classes. The sampling technique used is simple random sampling. The instrument used is a student learning achievement test, which is divided into pretest and posttest. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of data analysis using SPSS, it shows the results of calculating the Sig. = 0.178> α = 0.05 which means H_0 is accepted. So it can be concluded that there is no difference in learning outcomes between the cooperative learning models of the Numbered Head Together (NHT) and Group Investigation (GI) types on the learning outcomes of class X students of SMAN 8 Gowa.